Range of motion of lower-limb in senior male duathlon athletes - Cejudo, A.; Ruiz, I.; Sainz de Baranda, P.; Ayala, F.; Santoja, F. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2013)
The purpose of this study was to measure the lower-limb flexibility data in senior duatlon athletes. For it, the flexibility of the major lower-limb muscles was evaluated throughout 7 different peak joint ROM assessment tests (gastrocnemius, soleus, hamstrings, quadriceps, iliopsoas, gluteus and adductors). 15 in senior duatlon athletes tookpart in this study (32.7±7.85 years; 67.1±4.8 Kg; 172.9±2.8 cm).The results of this study define the normative data as: 10.4ºo for theiliopsoas, 40.3º for the gastrocnemius, 47.3º for the soleus, 50.7º for the adductors, 82.5º for the hamstrings, 116.7º for the quadricepsand, 145.9º for the gluteus. No significant differences were found between both legs and therefore muscle imbalances have been rejected.